MANAJEMEN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF MODERASI ISLAM WASATHIYYAH - Ahmad Saifudin (JIEM: Journal of Islamic Education and Manajemen, 2021)
Curriculum management today is increasingly getting attention from scientists who pursue the field of curriculum development, educational technology and education administration. This study is considered to occupy the most important part in the study of curriculum development and educational administration. This is natural, because the curriculum is an important component and is a very vital educational tool within the framework of the national education system. That is why, every educational institution, both formal and nonformal, must have a suitable and harmonious curriculum, appropriate to the position, function and role and purpose of the institution. Curriculum is an educational plan that summarizes all learning experiences provided for students in school. In an integrated curriculum philosophy, values, knowledge, and educational deeds. The curriculum is prepared by education experts or curriculum experts, experts in the field of science, educators, education officials, entrepreneurs and other elements of society. This draft is prepared with the intention of providing guidance to the implementers of education, in the process of guiding student development, achieving the goals aspired by students themselves, families, and communities. At this time the burden of learning and the number of subjects presented to children is very heavy. Therefore, all will only stuff students with a variety of materials that are more dominant in cognitive specs but not effective as a part of the purpose of character education. It is currently considered necessary to include Wasatiyah Islamic values in the Islamic education curriculum, which contains three concepts, namely values, character, and teachings. Therefore, the teacher is the key holder of the implementation and success of the curriculum. He is actually the planner, implementer, appraiser, and developer of the real curriculum.